Designed moisture and total moisture capacity of soils of the earthbed of motor roads - A. S. Aleksandrov; Т. V. Semenova; N. Р. Aleksandrova (Вестник СибАДИ, 2025)
Introduction. The calculation of road pavements according to strength criteria is performed for the design period of the year, when the soil moisture reaches its highest values. Such moisture is called design moisture and is established by determining the highest value at a given one-sided confidence probability, taking into account various corrections for the terrain, roadbed design and shoulder reinforcement. It would seem that everything is done correctly, but in some cases, the design moisture reaches high values, within 80...90% of the moisture at the fluidity limit. Such values of design moisture are greater than the full moisture capacity of some types of soil. In this case, the physics of the soil water saturation process is violated.Materials and methods. To calculate the total moisture capacity, the physical principles of engineering geology are used, based on a three-phase physical model of dispersed soil. In this model, each of the three phases (solid, liquid and gaseous) occupies a certain volume, and mineral particles and liquid have mass and weight. Based on this model, classical fundamental formulas are obtained that allow determining any physical characteristic of the soil. These fundamental dependencies are used to calculate the total moisture capacity. The calculation of the total moisture capacity is used when constructing a line of zero air content in the soil with its standard compaction. It is shown that the total moisture capacity depicted on this line is the highest moisture content for soil compacted to this state.Results. A method for calculating the total moisture capacity of the soil at different compaction coefficients is proposed. Its value in winter is taken as the minimum possible compaction coefficient, calculated taking into account the correction of Yu.M. Vasiliev and A.S. Eremin, which takes into account soil decompression during water freezing. The total moisture capacity of the soil, calculated with a minimum compaction coefficient, is a limit value that the calculated humidity cannot exceed.Conclusion. The authors’ ideas about the physical condition of soils are presented, according to which their calculated humidity cannot exceed the full moisture capacity at a given degree of compaction. Therefore, the value of the calculated humidity, expressed as a fraction of the humidity at the yield point Wр / WТ , is proposed to be limited to the relative value of the total moisture capacity Wsut / WТ .